Case-control accuracy study for TOY8 digital developmental screening tool for detecting delays among children aged 3–5 years - Toh, Teck-Hock; Lim, Yvonne Mei-Fong; Lee, Jeffrey Soon-Yit; Chan, Wai-Nam; Low, Zhen-Ying; Dahian, Kamilah; Chew, Siok-Cheng; Sivasampu, Sheamini; Law, William Kian-Boon; HSS, Amar-Singh (Frontiers in Pediatrics, 2025)
BackgroundDevelopmental delays affect up to 18% of children worldwide, particularly in disadvantaged populations. Early identification is critical; however, existing tools are often resource-intensive, language-dependent, and unsuitable for large-scale use in low- and middle-income countries. TOY8 is a smartphone-based, play-oriented developmental screening tool developed in Malaysia for children aged 3–5 years, available in Malay and English.PurposeTo validate TOY8 against the Griffiths Scales of Child Development, 3rd Edition (Griffiths III), determine optimal cut-offs, and assess parental perceptions of feasibility and acceptability.MethodsWe conducted a case-control study in Sarawak, Malaysia. Participants underwent TOY8 screening followed by Griffiths III assessment. Screening performance was evaluated using sensitivity, specificity, likelihood ratios, and receiver operating characteristic (ROC) analyses. Optimal cut-offs were derived by maximizing sensitivity while maintaining specificity at ≥0.6. Parental perceptions were measured using questionnaires.ResultsWe recruited 127 children (64 with developmental delay, 63 without). TOY8 demonstrated good sensitivity (0.77) for detecting any developmental delay and higher sensitivity for severe delay (0.84). Cognitive, speech-language, and fine motor domains demonstrated excellent discrimination (AUC 0.82–0.84), but lower sensitivity for gross motor (0.41–0.54) and personal-adaptive domains (0.59–0.64). Refined domain-specific cut-offs (ROC: 44–50) improve screening accuracy. Parents rated TOY8 highly: 98.4% found it easy/very easy to use, 99.2% useful, and 96.9% acceptable.ConclusionTOY8, the first digital developmental screening tool validated in Malaysia, demonstrated good accuracy, particularly in domains predictive of school readiness. Its brevity, ease of use, and strong parental acceptability support its feasibility for community and preschool settings. TOY8 offers a scalable solution for early detection in resource-limited contexts, directly advancing United Nations Sustainable Development Goal (SDG) 3 on health and well-being, and SDG 10 on reducing inequalities by improving access to developmental screening in underserved populations.